2020
DOI: 10.17650/2712-7672-2020-1-1-30-46
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioural therapy in virtual reality treatments across mental health conditions: a systematic review

Abstract: Background. Virtual reality (VR) has been effectively used in the treatment of many mental health disorders.However, significant gaps exist in the literature. There is no treatment framework for researchers to use when developing new VR treatments. One recommended treatment across a range of diagnoses, which may be suitable for use in VR treatments, is Cognitive Behavioural Therapy (CBT). The aim of this systematic review is to investigate CBT treatment methods that utilize VR to treat mental health disorders.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 111 publications
0
5
0
Order By: Relevance
“…Approximately 30% of young people who experience psychosis disengage from therapy (Doyle et al, 2014). These limitations might be solved by combining CBTp with virtual reality (VR) (Dilgul et al, 2020; Freeman et al, 2019; Pot‐Kolder et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 30% of young people who experience psychosis disengage from therapy (Doyle et al, 2014). These limitations might be solved by combining CBTp with virtual reality (VR) (Dilgul et al, 2020; Freeman et al, 2019; Pot‐Kolder et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…VR has the ability to represent social environments that trigger physiological and psychological responses equivalent to what a given context in the real world would create (Valmaggia et al, 2016). This makes VR environments ecologically valid for the treatment of various psychological disorders (Dilgul et al, 2020; Rus‐Calafell et al, 2018; Valmaggia et al, 2016). The technology allows social scenarios to be personalized, repeated and varied, and the therapist to observe discreetly and give feedback in real time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite encouraging predictions and rapid uptake of digitally enabled therapies, there is limited research into VR treatments for depression (Freeman et al, 2017;Dilgul et al, 2020). Furthermore, most VR research into mental health treatment has generally focused on its use one-to-one, in a clinic, with a health care professional (Dilgul et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Despite encouraging predictions and rapid uptake of digitally enabled therapies, there is limited research into VR treatments for depression (Freeman et al, 2017;Dilgul et al, 2020). Furthermore, most VR research into mental health treatment has generally focused on its use one-to-one, in a clinic, with a health care professional (Dilgul et al, 2020). It is suggested that delivering VR treatments in this format is unlikely to improve treatment accessibility (Price et al, 2014;Fairburn and Patel, 2017;Bucci et al, 2019;Ralston et al, 2019).…”
Section: Introductionmentioning
confidence: 99%